Portfolio Analysis Using Fama-French Five Factors Model And Its Relation With Behavioral Investor Theory: IDX-MES BUMN 17 Index - Ichsani, Sakina (LPPM Universitas Terbuka, 2025)
This study aims to analyze the performance of the sharia stock index named IDX-MES BUMN 17 on the Indonesia Stock Exchange (IDX) during the 2020–2024 period using the Fama-French Five Factor Model. This model evaluates the influence of five factors: company size, value factor, profitability factor, investment factor, and market risk. The data used are secondary data including historical stock prices, market index, and company fundamental data. Stocks are grouped into portfolios based on a combination of these factors. The analysis results indicate that investors with speculative and aggressive profiles should invest in SMBR and ELSA stocks. Young investors should invest in BRIS and TLKM stocks, while retirement/ institutional investors should invest in SMGR. Preserver investors are more suited to SMGR and IPCC, while Followers should invest in PTBA and TLKM. Independent/Individualists should choose ELSA, SMBR, PGAS, PTBA, BRIS, and TINS. Independent Active Accumulators can choose PTBA, ELSA, BRIS, ANTM, IPCC, TLKM, and PTPP. This study contributes to investors and investment managers in understanding the optimal portfolio structure that suits investors' risk preferences.